A STUDY OF WOMEN MANAGER’S SUCCESS FACTORS IN MULTINATIONAL ORGANIZATION - FROM BANGLADESH PERSPECTIVE - Hossain, Farhad (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
Women are getting an imperative part of the full population. However, women involvement is very insignificant in Bangladesh. In the last two decades, Bangladesh has experienced rapid economic growth. Economic growth has led to an upsurge in demand for managers and professionals. According to the Bangladesh Bureau of Statistics, the female labor force participation rate increased to 40% in 2019, compared to 4% in 1974. This change is much faster than the growth of the male labor force. Especially in Multinational Company women are now showing their talent and they occupy many upward posts in their career advancement. The key purpose of this paper is to find out the factors that help women to become a success in MNC’s. Many women in our country occupied many important posts in MNC’s, particularly in managerial mid-level post their presence is significant. This study use exploratory research to shed light on the various aspects that influence women’s actual behavior and performance in top positions, as well as the true reasons for women’s advancement to the top of organization. A survey questionnaire is distributed among 100 women managers who are occupied different positions in different MNC’s. The methodology employed in this study was quantitative research. To check the questionnaire’s validity, the researcher used IBM SPSS Statistics 20. From the results, we get some factors like personal, community, and organizational factors that have a huge impact on their success in MNC’s.